A conventional boy - Stross, Charles (Stross, Charles. Laundry files novel, 2025)
In this new Laundry Files adventure the fate of the world will literally depend on the roll of dice, twenty-sided dice, that is. In 1984, Derek Reilly was just another spotty teenage dungeon master growing up in middle England. But then a secret government agency tasked with suppressing magical intrusions received a tip-off and one midnight raid later, his life was turned upside down by the Satanic D&D Panic. Decades later Derek, now middle-aged and institutionalized, is a long-term inmate at Camp Sunshine, a center for deprogramming captured Elder God cultists. He's considered safe enough to edit the camp newsletter, and he even has postal privileges which he uses to run a play-by-mail game. After 25 years, Derek finally has reason to escape: a nearby D&D convention. While Derek's D&D games were full of fictional elder gods and world-ending threats, a LARP game at the con is a dread ritual designed to summon a great evil into our world, and it's up to Derek and his players to stop them. The fate of the world may depend on the contents of Derek's magic dice bag.--